The contributions of rural livelihood diversification towards household income-poverty alleviation in Madumeleng Village, Limpopo Province - Maake, Shadrack Manala (My University, 2017)
Although motivations vary across households, livelihood diversification is commonly adopted as a coping strategy against income-poverty and food insecurity in Africa. Income-poverty is disproportionately the main integral dimension of poverty in relative countries across Sub-Saharan Africa. This study investigated the extent to which rural livelihood diversification contribute to income-poverty alleviation in Madumeleng Village, South Africa. This exploratory research has adopted the methodological triangulation through qualitative and quantitative approaches. Additionally, these approaches were convenient for specific analysis of textual, factual, observation and conceptual data as well as to ensure credibility of the results. Moreover, normative design was applied to observe the relationship of livelihood diversification and income-poverty alleviation as the measurable variables of the study. Primary data was collected in Madumeleng Village through questionnaire survey which was administered to 144 respondents of the households. The households were selected through simple-random sampling and, purposively sampled traditional leader through interview schedule. The study argued that an increase in number of diverse livelihood activities strengthens ability and potential of the household to alleviate income-poverty. Notwithstanding poverty is multidimensional, findings of the study ascertained that most people embrace livelihood diversification as ideal route out of poverty. However, non-farm activities has been acknowledged as an important pathway out of income-poverty albeit prevalent barriers such as inadequate education, inaccessible formal credit facilities and fragmented infrastructure. The study recommended measures such as provision of quality rural infrastructure development and establishment of skills acquisition training programmes by local government authority, to widen access of the poor into non-farm activities and grant poor people an opportunity to eradicate entry barriers of high return livelihoods
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2017
Keywords: Madumeleng Village; Income-poverty; Livelihood; Poverty alleviation; Poverty; Income; Poverty -- Prevention; Poverty -- South Africa -- Limpopo